Planifier les trames vertes dans les aires urbaines : une alliance à trouver entre paysagisme et écologie - Monique Toublanc; Sophie Bonin (Développement Durable et Territoires)
Planning greenways in urban areas : find an agreement between landscape architecture and ecology. This paper aims at following the progress of the idea of natural continuity through the vocabulary, its meanings and its manners, in the documents of urban planning of two case studies in provincial and Parisian contexts (metropolitan area of Angers and Plain of Versailles). The question of the contribution of the landscape thinking to the idea of greenway is central. We try in particular to spot the recourse to the notion of landscape by highlighting its connections with the other objects or founding models of the public action on greenways. It also leads to notice the dominion of a process of naturalization: more and more types of spaces, are recognized as "nature" in the greenways.